Trade policy in developing countries - Buffie, Edward F. (Cambridge University Press, 2001)
"Trade Policy in Developing Countries is an analysis aimed at academics, graduate students, and professional, policy-oriented economists. It is the first work in the field to examine trade policy in an integrated theoretical framework based on optimizing dynamic models that pay careful attention to the structural features of developing country economies. Following a thorough critique of the debate on inward- vs. outward-oriented trade regimes, Buffie explores the main issues of concern to less developed countries in the areas of optimal commercial policy, trade liberalization, and direct foreign investment